2015
DOI: 10.1038/sc.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

Brain–computer interface targeting non-motor functions after spinal cord injury: a case report

Abstract: Study design: This is a case report. Objectives: The objective of this study was to report on a brain-computer interface (BCI) paradigm that is successfully used with an inpatient spinal cord injury patient. Setting: This study was conducted in an inpatient rehabilitation hospital. Methods: A 25-year-old man with a C5 burst fracture and subsequent tetraplegia (The American Spinal Injury Association) participated in this case study. He completed a brief battery of psychological, pain, cognitive and other screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Results showed an increase of such indexes that are associated with logical thinking, problem solving, and attentiveness to external stimuli, suggesting an effect of the performed training also on nonmotor functions. Salisbury and colleagues [ 48 ] presented a single-case feasibility study on a patient with spinal cord injury (SCI), where EEG-BCI was employed for reducing pain and improving nonmotor functions such as mood and cognition, as part of inpatient rehabilitation treatment. Even if no data are presented about the described therapeutic goals, the study supported the feasibility and tolerability of this approach in the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed an increase of such indexes that are associated with logical thinking, problem solving, and attentiveness to external stimuli, suggesting an effect of the performed training also on nonmotor functions. Salisbury and colleagues [ 48 ] presented a single-case feasibility study on a patient with spinal cord injury (SCI), where EEG-BCI was employed for reducing pain and improving nonmotor functions such as mood and cognition, as part of inpatient rehabilitation treatment. Even if no data are presented about the described therapeutic goals, the study supported the feasibility and tolerability of this approach in the patient.…”
Section: Resultsmentioning
confidence: 99%
“…for any invertible X, and the self-duality 11 The geometric mean of two positive matrices C1 and C2 has been studied since the 1970's by electrical engineers, physicists and matrix analysts. A closed-form expression for it is known.…”
Section: (C2 G) Now Construct the Tangent Space Tgm At G There Eximentioning
confidence: 99%
“…They concluded that this choice should be preferred for N small, which is in line with our theoretical analysis. Reference [11] proposed a simple data augmentation approach for improving the performance of the Riemannian MDM algorithm. A hierarchical MDM classifier for multi-class problem has been tested in [117].…”
Section: A Review Of Studies Applying Riemannian Geometry To Eegmentioning
confidence: 99%
See 1 more Smart Citation
“…The P300 wave has been widely used for brain-computer interfaces (BCIs) [3,4]. For example, the P300 speller [5] is designed to infer a user's intention solely from brain signals and is a valuable tool for individuals with physical disabilities [6][7][8]. A user focuses on a character among 36 candidates arranged in a 6 × 6 matrix (Figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%